The nexus between financial sector development and efficiency in Islamic microfinance: insights from the Asian region - Zainal, Nurazilah; Bakri, Mohammed Hariri; Che Bahrun, Che Nurul Huda; Kasim, Eley Suzana (People & Global Business Association, 2025)
Purpose: this study proposes to determine level of financial efficiency of IMFIs and to examine impact of financial sector development on financial efficiency among IMFIs. Design/methodology/approach: Dataset comprises 137 IMFIs from in Asia region from 2013 to 2019. In first stage analysis, Data Envelopment Analysis (DEA) was utilised, followed by Panel Regression Analysis in second stage. Findings: Findings indicate IMFIs demonstrate high level of financial efficiency, which suggests they are financially efficient in long-term operations. Meanwhile, domestic to private credit sector and number of automated teller machine are found positively significant to influence financial efficiency of IMFIs. Research limitations/implications: Financial efficiency among significant aspect to contribute achievement of Microfinance as effective tool to eradicate poverty. However, Islamic Microfinance (IMFIs) experience obstacles when 700 million Muslim population has been found to live in extreme poverty which overclaimed its role in poverty agenda. Moreover, commercial banks started to offer similar products with IMFIs which possibly exposes vulnerability of IMFIs as it creates intense competition. Since IMFIs nowadays become an integral part of banking system, impact of financial sector development should be put into consideration. Originality/value: This study provides policymakers valuable insights to establish conducive regulatory framework that fit Shariah principle which simultaneously boost efforts of zero poverty.